Skin Cancer Back to Basics: Anogenital Squamous Cell Carcinoma. Issue 2 (March 2022) - Dhillon, Soneet; Lake, Eden
ABSTRACT: Anogenital squamous cell carcinoma is rare but an often-invasive malignancy that is becoming an increasingly prevalent public health problem. Infection with high-risk human papillomavirus variants plays a critical role in disease progression and occurrence. Immunosuppressive treatment, positive HIV status, number of sexual partners, and history of smoking increase neoplastic progression. Early diagnosis and treatment are pivotal in managing anogenital malignancies to improve quality of life and minimize extensive surgical excision. This article reviews lesion categorization, epidemiology, human-papillomavirus-driven dysplastic epithelial changes, risk factors, diagnostic criteria, treatment options, and prophylactic measures to improve patient outcomes.